Uma câmera para os quilombolas: representações imagéticas de si e da cultura negra em Ourém-PA - AGUIAR, Karollinne Levy (Universidade Federal do Pará, 2017)
The thematic of this work deals with the quilombola photography and its object are the image representations that quilombola children, from the black community “Mocambo”, in Ourém, in the northeastern part of Pará, construct about themselves and their culture. The theoretical approach seeks to relate Visual Arts, Visual Anthropology and Post Colonial Studies to substantiate comprehensions towards the relations and the senses these individuals, within their creative process, let see in the constitutive movement of photography as an artwork with its interfaces with culture, memory and quilombola identity in Amazon. To obtain such objectives, the methodology parts from oral history and image analysis, through ethnographic exercises and image workshops with quilombola children and teenagers. In this sense, at the first moment, these individuals assume the role of visual artists to compose registry about them and about the most significant local landscape, according their choices. At the second moment, we put ourselves listening to the meanings attributed to the records by their creators, seeking to capture connections with quilombola modes of living. We argue that the study of objects of art, taking their joints with the place, their subjects and their stories, constitutes strong evidence of alliances between art and life. On the other hand, this work seeks to uncover and appreciate looks that these people construct about themselves and their culture, which can be an important clue about their silences in visual narratives and unexplored intercultural perspectives through the research in Arts in Amazon and in other regions of Brazil.